Successive line-locked C iv doublets in quasar SDSS J115122.14+020426.3. Issue 2 (31st July 2020) - Lin, Ying-Ru; Lu, Wei-Jian
ABSTRACT: Rodríguez Hidalgo et al. (2013, ApJ, 775, 14) have reported the transition of a C iv mini-broad absorption line (mini-BAL) into a BAL in quasar SDSS J115122.14+020426.3 (hereafter J1151+0204). Based on the two-epoch spectra obtained from the Sloan Digital Sky Survey, we further investigate the three BAL systems (systems A, B and C) in J1151+0204. First, we confirm that the absorption-line variability in J1151+0204 is most likely caused by the change in ionization in response to the continuum variation, according to at least the following observational factors: coordinated strengthening is detected between multiple absorption troughs, and the continuum shows obvious weakening. According to photoionization simulations, asynchronized variability between the continuum and absorption lines indicates that the mini-BAL (system A) of J1151+0204 actually represents the state of a higher ionization level and lower C iv column density of the outflow, while its BAL identifies the state of a lower ionization level and higher C iv column density. Second, we find a rare case of a quintuple, which is due to four successive line-locked C iv doublets, within system C. This indicates that these outflow clouds have achieved a high degree of clumpiness, and that the radiative forces play a significant role in the acceleration process of these clumpy outflow clouds.